Towards bootstrapping F-theory - Behan, Connor [UNESP]; Chester, Shai M.; Ferrero, Pietro (Springer Nature, 2024)
We consider type IIB string theory with N D3 branes and various configurations of sevenbranes, such that the string coupling gs is fixed to a constant finite value. These are the simplest realizations of F-theory, and are holographically dual to rank N Argyres-Douglas conformal field theories (CFTs) with SU(2) and SU(3) flavor groups, and Minahan-Nemeschansky CFTs with E6, E7 and E8 flavor groups. We use the Seiberg-Witten curves of these theories to compute the mass deformed sphere free energy F (m) at large N in terms of novel matrix models with non-polynomial potentials. We show how F (m) can be used along with the analytic bootstrap to fix the large N expansion of flavor multiplet correlators in these CFTs, which are dual to scattering of gluons on AdS5 × S3, and in the flat space limit determine the effective theory of sevenbranes in F-theory. As a first step in this program, we use the matrix models to compute the log N term in F (m) and thereby fix the logarithmic threshold in the AdS5 × S3 holographic correlator, which matches the flat space prediction.
Keywords: 1/N Expansion; AdS-CFT Correspondence; F-Theory; Scale and Conformal Symmetries